Contributors’ Satisfaction Towards the Social Security Fund in Nepal - Dhungel, Suraj; Subedi, Manoj; Shrestha, Rina (Journal of Emerging Management Studies, 2026)
Purpose – This study examines contributors’ satisfaction towards the Social Security Fund in Nepal, focusing on four key factors: level of compensation, financial proficiency, retirement planning, and SSF coverage.Design/methodology/approach – A combined descriptive and causal research approach was used. Data were collected from 409 SSF contributors in Nepal using a structured questionnaire that included demographic data, involvement in the SSF, and perceptions of the SSF, measured on a five-point Likert-style scale. Descriptive statistics, Pearson correlation analysis, and multiple linear regression were conducted using SPSS version 26 and Microsoft Excel to assess the relationships among compensation, financial skills, retirement plans, SSF coverage, and SSF contributors' satisfaction.Findings – The descriptive findings showed that the SSF coverage provided the highest average rating followed by financial proficiency, retirement plan, and contributor satisfaction. The correlations were statistically significant and positive with each of the independent variables and contributor satisfaction; the strongest relationships were with the retirement plan and the SSF coverage. The regression model accounted for 58.3% of the variance in contributor satisfaction. Conversely, financial proficiency had a negative but not statistically significant effect on contributor satisfaction.Conclusion – Contributors’ satisfaction with the SSF in Nepal remains moderate overall. Satisfaction is driven primarily by perceptions of retirement security and the adequacy of fund coverage rather than by short-term financial returns or compensation. Strengthening retirement-related schemes, broadening coverage, and improving transparency and service delivery are likely to enhance contributor satisfaction and support the SSF's long-term sustainability.Originality/value – This study contributes to the limited body of empirical research on Nepal’s contribution-based SSF by jointly examining compensation, financial proficiency, retirement planning, and fund coverage as determinants of contributor satisfaction. This integrated perspective has not been widely addressed in the Nepalese context.